2015
DOI: 10.1155/2015/145828
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Vitamin D, Erythropoiesis, and the Renin-Angiotensin System

Abstract: For many years deficiency of vitamin D was merely identified and assimilated to the presence of bone rickets. It is now clear that suboptimal vitamin D status may be correlated with several disorders and that the expression of 1-α-hydroxylase in tissues other than the kidney is widespread and of clinical relevance. Recently, evidence has been collected to suggest that, beyond the traditional involvement in mineral metabolism, vitamin D may interact with other kidney hormones such as renin and erythropoietin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 107 publications
2
76
1
Order By: Relevance
“…Th e fi nding of lower red blood cell and hemoglobin concentrations in VDD patients is in line with the published data on VDD association with anemia in CKD patients. Although the exact mechanism is unknown, VDD may impair erythropoiesis via immune activation within the bone marrow 23 . Out of 40 study patients, only 10 (25%) had no ED (ED 0 group), 20 patients had mild (ED 1) and seven patients mild to moderate ED (ED 2), while three patients had severe ED (ED 4 group).…”
Section: Table 2 Comparison Of Non-ed (Ed 0) Versus Patients With Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e fi nding of lower red blood cell and hemoglobin concentrations in VDD patients is in line with the published data on VDD association with anemia in CKD patients. Although the exact mechanism is unknown, VDD may impair erythropoiesis via immune activation within the bone marrow 23 . Out of 40 study patients, only 10 (25%) had no ED (ED 0 group), 20 patients had mild (ED 1) and seven patients mild to moderate ED (ED 2), while three patients had severe ED (ED 4 group).…”
Section: Table 2 Comparison Of Non-ed (Ed 0) Versus Patients With Anmentioning
confidence: 99%
“…A simplifi ed 5-item version of the International Index of Erectile Function (IIEF-5) was used as a diagnostic tool for ED evaluation 13 and to further divide study subjects into diff erent ED categories. According to the IIEF-5 score, the patients were categorized as no ED (ED 0; score [22][23][24][25], ED 1 (score 17-21), ED 2 (score 12-16), ED 3 (score 8-11) and ED 4 group (score ≤7). Th e groups were then compared according to serum levels of 25(OH)D, complete blood count, hemoglobin, PTH, fasting blood glucose, creatinine, high-sensitivity C-reactive protein (hs-CRP), cholesterol and triglycerides per body mass index (BMI), duration of renal replacement therapy (RRT) before TX, and kidney graft duration until analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Atkinson et al (23) reported similar relationships in healthy children and adolescents. Several possible mechanisms for the association between vitamin D and anemia have been proposed, such as a direct stimulatory proliferative effect of vitamin D on bone marrow cells via VDR (24), silencing of inflammatory reactions that lead to anemia or chronic diseases (25) or parathyroid hormone (PTH)-dependent alteration in erythrocyte osmotic resistance (26). However, so far, the results of observational studies have not been confirmed by RCT (27)(28)(29).…”
mentioning
confidence: 99%
“…Vitamin D metabolites have renoprotective effect by antiproteinuric, anti-inflammatory, and immunomodulatory properties and by suppression of renin-angiotensin-aldosterone system (RAAS) [22]. Low serum 25-OH-D level activates (RAAS) and increases fibroblast growth factor which are associated with progression of renal injury [23, 24].…”
Section: Discussionmentioning
confidence: 99%